A switch in the formation of alternative DNA loops modulates lambda site-specific recombination. - Moitoso de Vargas, L (1991)
The virally encoded Xis protein is one of the components in the site-specific recombination reactions of bacteriophage lambda. It is required for excisive recombination and inhibits integrative recombination. The mechanism of Xis inhibition of the integration reaction was investigated by methylation protection assays (footprinting analyses) in conjunction with recombination assays. Xis is shown to mediate the formation of a specific attP looped structure involving cooperative and competitive long-range interactions among integrase, integration host factor, and Xis proteins. This higher-order structure precludes supercoiled attP from engaging in the productive partner interactions that lead to execution of the first strand exchange in integrative recombination. In addition to its previously characterized role in excision, Xis-induced DNA bending is postulated to act as a regulatory switch (in an alternative loop mechanism) that converts the attP intasome from an integrative-competent complex to a nonreactive one.